Klinefelter’s syndrome in azoospermic infertile males of Vidarbha region, Central India - Maske, Gajanan L.; Kannamwar, Archana D. (International Journal of Research in Medical Sciences, 2016)
Background: Infertility was defined as involuntary failure of conception in a married couple after 1 year of regular unprotected intercourse. Male factor infertility is a distressing condition that adds to the psychological trauma to majority of couples. The widely accepted methods of screening for infertility in males are semen analysis and cytogenetic studies. Klinefelter syndrome, with an incidence of 1:600 male newborns, is the most frequent form of male hypogonadism. Methods: 30 non-obstructive azoospermic infertile males were selected for present study. For each subject, chromosomal analysis was carried out by conventional as well as giemsa trypsin giemsa (GTG) technique in cytogenetic laboratory. Total 25 metaphases i. e. 15 conventional and 10 G-banded metaphases were analyzed, in each case. In cases with chromosomal abnormalities, total 45 metaphases i. e. 25 conventional and 20 G-banded metaphases were studied. Selected metaphases were photographed using CCD camera. Results: Three subjects had a chromosomal count of 47 in all the metaphase studied. The additional chromosome was closely matching with the X chromosome. Hence the karyotype showed numerical aberration with an extra ‘X’ chromosome i. e. 47, XXY suggestive of Klinefelter’s syndrome. This was confirmed by G-banding. All of the three subjects had bilateral testicular atrophy and one had typical features of Klinefelter’s syndrome except gynecomastia. Conclusions: On cytogenetic analysis of 30 azoospermic infertile subjects, chromosomal abnormality of 47, XXY (Klinefelter’s syndrome) was found in 3 subjects. The total percentage of Klinefelter’s syndrome in present study comes to 10%.